PENGARUH BEBAN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA SUBINSTALASI BINATU DAN CSSD RUMAH SAKIT UNIVERSITAS INDONESIA - Chairul Fadli; Irwansyah Irwansyah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to determine the effect of workload and physical work environment on employee performance in the laundry and CSSD sub-installation of the University of Indonesia Hospital. This research method uses an associative quantitative method, with a population of 32 respondents who are employees of the laundry and CSSD sub-installation of the University of Indonesia Hospital. Data analysis uses validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficients of determination with the help of the SPSS program. The results of the study indicate that partially the workload has a positive and significant effect on employee performance with a t-count value of 5.512> 2.045 and a significance value of 0.000 < 0.05. The physical work environment also has a positive and significant effect on employee performance with a t-count value of 6.112> t-table 2.045 and a significance value of 0.000 <0.05. Simultaneously, workload and physical work environment significantly influence employee performance with an F-count value of 18.253 > F-table 3.33 and a significance of 0.000 < 0.05. The coefficient of determination is 0.527 or 52.7% while the remaining 47.3% is influenced by other factors outside the study.